Quality of Abstracts Reporting in Periodontal Randomized Controlled Trials: A Descriptive Analysis - Fahad Alharbi; Khalid Gufran; Muzammil M. Ahmed; Rawda O. Alghabban; Mohammad Meish Almohammadi; Abdullah S. Almutairi (Journal of Pharmacy and Bioallied Sciences)
The quality of randomized controlled trials (RCTs) abstracts greatly impacts the way readers perceive interventional outcomes, influencing their scientific applicability. Recent data about the quality of periodontal RCT abstracts that have been published is lacking. Thus, the aim of this study is to assess the reporting quality of abstracts in RCTs published in periodontal journals in recent years. The study is descriptive and cross-sectional, surveying the abstracts of RCTs published in the Journal of Periodontology (JOP), Journal of Clinical Periodontology (JOCP), and Journal of Periodontal Research (JOPR) between 2018 and 2022. The assessment of reporting quality was performed employing the CONSORT criteria for abstracts of RCTs. The quantitative values for each item on the CONSORT checklist for all published RCT abstracts were derived by descriptive statistical techniques, including univariate analysis. Comparisons were drawn between the journals and the different variables included in the study. The investigation identified 176 RCTs (11.7%) out of a total of 1506 articles published in these three journals over a period of four years. The primary observation of this research is that the mean quality scores were a mere 52.36 ± 9.9 for all the published periodontal RCTs abstracts. JOCP obtained the highest quality scores (54.7 ± 10.5), followed by JOPR (52.4 ± 9.9) and JOP (49.1 ± 7.9). RCT abstracts from Europe had higher reporting quality, whereas those from Africa were the lowest. The trials carried out in mixed settings showed better quality in the reporting of abstracts compared to those conducted in university, private, or governmental settings. RCTs with more than six authors and statisticians involved showed higher quality scores. These results are not indicative of a substantial improvement when compared to previous years (2015–2018). Abstracts of RCTs reported are below par in the preeminent periodontology journals. There has been no discernible progress over the years, notably in terms of blinding, the randomization description, and the disclosure of potential harms.